Associations between serum albumin and serious non-AIDS events among people living with HIV. (24th August 2018) - Ronit, Andreas; Hatleberg, Camilla I.; Ryom, Lene; Bonnet, Fabrice; El-Sadr, Wafaa; Reiss, Peter; Weber, Rainer; Pradier, Christian; De Wit, Stephane; Law, Matthew; d'Arminio Monforte, Antonella; Lundgren, Jens; et al.
Abstract : Objective: Lower serum albumin (sAlb) has been associated with an increased risk of mortality and AIDS among people living with HIV and may be associated with the development of serious non-AIDS events (SNAEs). We evaluated the long-term association between sAlb and the risk of SNAEs. Design: Prospective multinational cohort study. Methods: D:A:D participants without SNAEs were followed from first routine sAlb value to the first of a new SNAE [cardiovascular disease (CVD), end-stage liver disease (ESLD), end-stage renal disease (ESRD), non-AIDS malignancy (NADM), death from non-AIDS cause], AIDS-death, 6 months after last visit or 1 February 2016. Poisson regression was used to determine associations between sAlb and a new SNAE, CVD, or NADM event, with adjustment for potential confounders. Models additionally tested whether the associations were modified by age, follow-up time, smoking status, CD4 and viral load. Results: Of 16 350 participants (71.8% male, median age 44 years), 1463 developed an SNAE (371 CVD, 200 ESLD, 40 ESRD, 553 NADM, 299 deaths from other non-AIDS causes) over 80 264 person-years. Increased sAlb was associated with a decreased risk of an SNAE [adjusted rate ratio per 5 g/l: SNAE 0.79 (95% confidence interval: 0.76, 0.83); CVD 0.87 (0.80, 0.94); NADM 0.88 (0.82, 0.95)]. The association did not appear to wane with additional years of follow-up ( P -interaction = 0.79) but was stronger for current smokers than for never smokers ( P -interaction <0.01). Conclusion: sAlb is a durable risk factor for SNAE. Future studies are needed to determine the mechanism underlying this association and to evaluate the value of sAlb in predictive tools. Abstract : Supplemental Digital Content is available in the text